2021
DOI: 10.1002/mmce.22809
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized quad‐band filter with improved selectivity using split ring resonators and metallic strips

Abstract: A miniaturized bandpass filter of quad-band response with high selectivity is reported in this paper. The developed filter utilizes two sets of symmetric open-ended split-ring resonators (SRR), L-shaped and C-shaped strips along with rectangular stubs. Initially, open-ended SRR is connected with a C-shaped metallic strip to serves as a dual passband filter. Then by adding another SRR along with L-shape metallic strip and rectangular stub, it was converted into triple band and quad-band respectively. The operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A split-ring resonator (SRR) can serve as the basis for constructing a negative permeability stopband structure [6]. Numerous studies [7][8][9] have shown that split-ring resonators can be used to create bandpass and band-stop filtering structures. Complementary split-ring resonators (CSRRs) were used to construct a stopband microstrip line in 2004 by Falcone et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…A split-ring resonator (SRR) can serve as the basis for constructing a negative permeability stopband structure [6]. Numerous studies [7][8][9] have shown that split-ring resonators can be used to create bandpass and band-stop filtering structures. Complementary split-ring resonators (CSRRs) were used to construct a stopband microstrip line in 2004 by Falcone et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the number of resonators, multimode resonators (MMRs) [9]- [11] are frequently employed. The commonly used structures for multi-mode resonators are stub-loaded resonators [12,13], steppedimpedance resonators [9,12,14] and ring resonator [15]. In [14], a quint-wideband BPF was presented, it adopted spiral and open-loop coupled structures with mixed electric and magnetic coupling (MEMC) to reduce design complexity, but the circuit size was relatively large.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, researchers are more focused on developing miniaturized quad-, penta-, and sext-band BPFs. Different design topologies have been adopted to develop quad-band BPF [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. A popular method to design a quad-band BPF is by using stub-loaded topology [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%